Prevalence of Escherichia coli O157 : H7 and Their Verotoxins and Salmonella spp. in Processed Poultry Products. Issue 3 (23rd July 2013) - Karadal, Fulden; Ertas, Nurhan; Hizlisoy, Harun; Abay, Secil; Al, Serhat
Abstract This study was carried out to investigate the presence of Escherichia coli O157 : H7 and their verotoxins as well as Salmonella spp. in processed poultry products. A total of 100 samples of cordon bleus (n = 20), chicken nuggets (n = 20), chicken burgers (n = 40) and chicken meatballs (n = 20) were analyzed. The E. coli O157 (but not H7) strain was isolated from one (1%) out of 100 samples. This isolate were obtained from chicken burgers. Multiplex polymerase chain reaction confirmed two genotypes, namely rfbO157 and stx1 genes. None of the samples was contaminated with Salmonella spp. These results demonstrate that processed poultry products may be sporadically contaminated with E. coli O157 strains that are potentially pathogenic for humans. Practical Application The growth of E. coli O157 and Salmonella in processed poultry products are dependent on poultry carcasses used as raw material, hygienic application during the process and the storage temperature. Potentially pathogenic agents for humans E. coli O157, which was obtained in this study, and Salmonella spp. should be controlled by heat‐treatment.